Elevated AQP1 Expression Is Associated With Unfavorable Oncologic Outcome in Patients With Hilar Cholangiocarcinoma. (August 2017) - Li, Chunxiang; Li, Xiaofu; Wu, Linfeng; Jiang, Zheng
Background: Hilar cholangiocarcinomas are malignant tumors with a poor prognosis. An early prediction of prognosis for patients may help us determine treatment strategies. Aquaporin 1 is a cell membrane channel involved in water transport, cell motility, and proliferation. Increasing evidences showed that aquaporin 1 played a role in tumor prognosis and diagnosis. The purpose of this study is to evaluate the role of aquaporin 1 in hilar cholangiocarcinoma. Methods: Here, we analyzed messenger RNA expression data of genes function as bile secretion in a data set of 169 samples using the R2 bioinformatic platform (http://r2.amc.nl ). Quantitative polymerase chain reaction was performed to verify the gene expression in 17 hilar cholangiocarcinoma samples. Immunohistochemistry was also performed in a series of specimens from 62 hilar cholangiocarcinoma tissues, and its clinical significance was assessed by clinical correlation and Kaplan-Meier analyses. Results: All data were analyzed using the R2 web application, aquaporin 1 was selected for further analysis. The significant expression variation of aquaporin 1 among 17 cases with cholangiocarcinoma was also found using quantitative polymerase chain reaction. The expression level of aquaporin 1 protein significantly correlated with tumor-node-metastasis stage ( P = .002) and overall survival time ( P = .010). Higher aquaporin 1 expression indicated poor prognostic outcomes ( P <.05, log-rank test). Multivariate analysis also showed strong aquaporin 1 protein expression was an independent adverse prognosticator in hilar cholangiocarcinoma ( P = .002). Conclusion: This study highlighted the prognostic value of aquaporin 1 in hilar cholangiocarcinoma. Strong aquaporin 1 expression predicts poor survival, regardless of pathological features. Immunohistochemical detection of aquaporin 1, as a prognostic marker, may contribute to predicting clinical outcome for patients with hilar cholangiocarcinoma.